ACTINOMYCETES ASAL RHIZOSFER TUMBUHAN MANGROVE DI KAMPUNG WAMESA DISTRIK MANOKWARI SELATAN KABUPATEN MANOKWARI SEBAGAI PENGHASIL ANTIMALARIA - Tati Tati; Hermawaty Abubakar; Yenni Y Salosa (VOGELKOP: Jurnal Biologi, 2023)
Malaria is a public health problem in Indonesia and several other countries. The rhizosphere is a natural habitat for various soil microorganisms. The mangrove rhizosphere area is very potential for microbial growth, especially Actinomycetes. This study aims to identify and test the In Vitro antimalarial ability of the best isolates isolated from the mangrove rhizosphere of Wamesa Village based on the results of tests on bioactive compounds. In this study, 3 pure Actinomycetes isolates were obtained, namely T1, T2 and T3 which were grouped into 3 three groups (colour grouping) based on the color of the aerial mycelium, the substrate mycelium, and the color that diffuses in the media. The test results for the content of the Actinomycetes bioactive compounds showed that isolates T1 and T2 contained alkaloids, saponins, flavonoids and tannins, while isolate T3 contained alkaloids, saponins and tannins. The results of the study of the antimalarial activity of Actinomycetes isolates against P. falciparum in vitro showed that isolate T1 had the highest inhibition percentage at a concentration of 10-2 μg/mL, namely 83.33%, and the lowest inhibition at a concentration of 10-12 μg/mL, namely 58.33%. Isolate T2 had the highest inhibition percentage at a concentration of 10-3 μg/mL, namely 95.38% and the lowest inhibition, namely 10-12 with an inhibition value of 64.62%. The IC50 values of isolates T1 and T2 were 1.95x10-15 µg/mL and 1.45 x 10-15 µg/mL, respectively.